Grammatical Relations and Semantic Roles of Arguments in English Verbs of Transfer “Convey” - Janardana Dwipayana, Ida Bagus; Arka, I Wayan; Sedeng, I Nyoman (Udayana Journal of Social Sciences and Humanities; Vol 7 No 1 (2023): UJoSSH, February 2023, 2023)
This study entitled Grammatical Relations and Semantic Roles of Arguments in English Verbs of Transfer “Convey”. It focused on grammatical relations and semantic role of argument within a certain argument structure. The particular and only data source of this study is Corpus of Contemporary American English. This study used accidental sampling method. Therefore, every data found are constructed with transfer verb “convey” proposed by Levin. Base theories of the analysis are Grammatical Relation and Semantic Role by Kroeger, while it supported by theory of Proto-Roles by Dowty and Taylor. The data representation chosen are presented both in formal and in-formal method. There are 3 different argument structures found within the 100 samplings. Transitive Structure turn out to be the most dominant structure, while the other which are intransitive and ditransitive are reasonably represented. All the grammatical relations are found, they are Subject, Object, Oblique, and Adjunct. In the other hand, all the semantic roles are found except stimulus, beneficiary, and accompaniment. Terms proto-agent and proto-patient supports the mapping of the semantic content. Some roles such as theme and instrument have different lexical understanding. It divided into three terms; physical, perceptive, abstract entities. Specifically, the agent classified into three different indication they are non-symbolic agent, metaphorical agent, abstract agent.